Extra-oral receptors sensitive to ligands that act in extra-oral tissues. - Kathleen W. Higgins (3117753) (2025)
(A) schematic illustrating our in vitro functional assay inside a human embryonic kidney (HEK293T) cell. Activation of the TAS2R by an extracellular bitterant causes calcium release from the endoplasmic reticulum, which reacts with coelenterazine and clytin-II in the mitochondrial matrix to produce blue light. (B) Raw readout of luminescence during a positive bitter assay, with bullfrog TAS2R61 as an example. The orange curve shows the data for aflatoxin B1 and the gray curve is for the buffer condition. For clarity, only one replicate is shown for each condition. (C) Diagram showing phylogenetic tree, heatmap for expression data, and heatmap for receptor activity. Phylogenetic tree is subset from the large tree in S15 Fig. Receptors not responding to any tested substances in our functional assay were represented in gray. Expression data are measured in fragments per kilobase of transcript per million mapped reads (FPKM) and are shown on a log scale, with 0.1 added to allow for FPKM = 0 values. Functional assay data are white if not significantly higher than buffer (two-sided Welch’s t-tests corrected by Benjamini-Hochberg adjustment with α = 0.05). Significant data are normalized to the largest chemical to buffer difference for each receptor, with 100% of receptor maximum shown in dark green with a linear scale down to a 0% difference in white. Chemicals are split into ecologically relevant substances (left) and classic bitterants (right), and then alphabetized within each group. Fungal toxins, frogs’ toxins, and natural alkaloids are represented in orange, purple, and light blue, respectively. (D) Dose response relationships for eight important receptor/ligand pairs (n = 6–9, mean ± SEM). Lines are represented in orange for aflatoxin B1, green for cinobufagin, and purple for marinobufagenin. Insets show the magnifying displays for a subset of ligands. Asterisks indicate minimum concentrations where T2R-transfected cells showed responses significantly higher than those in the lowest concentration (p < 0.05, Dunnett’s tests).